Complex Optical Investigation of Sodium Superoxide Loaded Phosphovanadate Glass System in Ultra-Violet and Visible Region - Barde, Rajesh; Nemade, Kailash; Waghuley, Sandeep (Trends in Sciences, 2022)
Sodium superoxide loaded phosphovanadate based glass systems were prepared from a mixture of vanadium pentoxide (V2O5), phosphorus pentoxide (P2O5) boric acid (H3BO3) and sodium superoxide (NaO2) using a melt-quenching method. Amorphous phase of as-prepared glass system confirmed using XRD technique. Surface morphology of glass system studied using scanning electron microscope. Ultraviolet-visible spectroscopy was employed to extract complex optical parameters like direct and indirect optical band gap, Urbach energy, refractive index, complex dielectric constant and optical conductivity. The absorption bands in the region 200 - 400 nm are recognized to the ligand-to-metal charge transfer. The region of 400 - 600 nm is ascribed to the pair excitation processes. The refractive index increases initially and then decreases for 15 and 20 mol % of NaO2 due non bridging oxygen (NBO) atoms. The 25 mol % of NaO2 sample shows maximum value of extinction coefficient and refractive index. The direct and indirect band gap energies vary in between 2.067 to 1.824 eV and 1.869 to 1.495 eV, respectively. With increase in concentration of NaO2, the effective band gap of NaO2 decreases because band edge shifted into forbidden gap due to increase in defect levels below the conduction. This primary report on sodium superoxide loaded phosphovanadate based glass systems opens wide avenue for battery and supercapacitor applications. Tailing in the bandgap was observed and found to obey Urbach rule. HIGHLIGHTS Sodium superoxide-phosphovanadate glass system prepared by melt-quenching method Complex optical properties of prepared glass system studied successfully Glass system have characteristics of trapping of light Also, glass system has ability to slow down light GRAPHICAL ABSTRACT